The Effect of Different Types of Fertilizers on The Growth and Yield of Large Chili Plants (Capsicum annuum L.) - Aprilia, Bunga; Indarwati, Indarwati; Herawati, Jajuk (Journal of Applied Plant Technology, 2025)
This study is meant to check out how giving different types of organic fertilizer, like Nutrizim granules, Nutrizim crumb, and liquid rabbit urine, affects the growth and yield of large chili peppers (Capsicum annuum L.). The research method used a Randomized Block Design (RBD) with five treatments and four replicates. The study was conducted from late May to early October 2024 in an open field at Pondok Pesantren Bhakti Bapak Emak, Jombang. The results showed that (a) the application of Nutrizim Granule and Crumb fertilizers significantly affected the growth of large chili plants (plant height, number of leaves, number of branches, and stem diameter). However, it did not significantly affect the yield of large chili plants (Total Fruits, Fruit Length, Fruit Diameter, Fruit Weight, Fruit Weight Per Plant, and Fruit Volume). (b) The application of Nutrizim Granular and Crumb Fertilizer combined with liquid rabbit urine organic fertilizer significantly affected the growth of large chili plants (Plant Height, Number Of Leaves, Number Of Branches, And Stem Diameter). However, it did not significantly affect the yield of large chili plants (Total Fruits Per Plant, Fruit Length, Fruit Diameter, Fruit Weight, Fruit Weight Per Plant, And Fruit Volume). Even though, large chili plants treated with the experimental treatments were able to produce a total of 8.46 fruits per plant, fruit length of 7.79 cm per fruit, fruit diameter of 1.05 cm per fruit, fruit weight of 6.00 g per fruit, fruit weight per plant of 47.39 g, and fruit volume of 6.55 ml per fruit.